STUDY OF CELLULOSE PARACRYSTALLINITY - Michael Ioelovich; Alex Leykin; Oleg Figovsky (BioResources, 2010)
The paracrystallinity of cellulose samples was studied with a complex of investigation methods including X-ray, NMR, sorption, calorimetry, and some others. It was found that the paracrystalline fraction of cellulose is located on the surface of crystallites as thin monomolecular layers having an average thickness of 0.4 nm. The paracrystalline surface layers have distorted and loose packing that is characterized by a high distortion parameter δp = 0.18, increased specific volume Vp=0.664 cm3/g, and decreased specific gravity ρp= 1.51 g/cm3. The paracrystalline fraction of the crystallite can be quantified by the parameter (α), which has an expressed influence on some properties of cellulose. Increasing of the α-value causes expansion of inter-plane distances in the C1 unit cell, as well as promotes mercerization and dissolution of cellulose.